Flexible Broadband Graphene Photodetectors Enhanced by Plasmonic Cu3−xP Colloidal Nanocrystals. Issue 42 (22nd September 2017) - Sun, Tian; Wang, Yongjie; Yu, Wenzhi; Wang, Yusheng; Dai, Zhigao; Liu, Zeke; Shivananju, Bannur Nanjunda; Zhang, Yupeng; Fu, Kai; Shabbir, Babar; Ma, Wanli; Li, Shaojuan; et al.
Abstract: The integration of graphene with colloidal quantum dots (QDs) that have tunable light absorption affords new opportunities for optoelectronic applications as such a hybrid system solves the problem of both quantity and mobility of photocarriers. In this work, a hybrid system comprising of monolayer graphene and self‐doped colloidal copper phosphide (Cu3− x P) QDs is developed for efficient broadband photodetection. Unlike conventional PbS QDs that are toxic, Cu3− x P QDs are environmental friendly and have plasmonic resonant absorption in near‐infrared (NIR) wavelength. The half‐covered graphene with Cu3− x P nanocrystals (NCs) behaves as a self‐driven p–n junction and shows durable photoresponse in NIR range. A comparison experiment reveals that the surface ligand attached to Cu3− x P NCs plays a key role in determining the charge transfer efficiency from Cu3− x P to graphene. The most efficient three‐terminal photodetectors based on graphene‐Cu3− x P exhibit broadband photoresponse from 400 to 1550 nm with an ultrahigh responsivity (1.59 × 10 5 A W −1 ) and high photoconductive gain (6.66 × 10 5 ) at visible wavelength (405 nm), and a good responsivity of 9.34 A W −1 at 1550 nm. The demonstration of flexible graphene‐Cu3− x P photodetectors operated at NIR wavelengths may find potential applications in optical sensing, biological imaging, and wearable devices. Abstract : High‐performance and broadband photodetectors based on the hybrid graphene‐Cu3− x P nanocrystal structure are demonstrated. A flexible graphene‐Cu3− x P photodetector on polyethylene naphthalate substrate capable of infrared (IR) light detection is realized and the photocurrent shows no obvious degradation even after bending 5000 times, indicating very good flexibility. This work paves a new way for fabrication of broadband and flexible IR optoelectronic devices.